Field quantization in quantum plasmas: Photon and plasmon charge and mass. Issue 2 (26th July 2021) - Mendonça, J.T.
Abstract: We study electromagnetic field quantization in isotropic quantum plasmas, thus connecting two distinct problems of quantum plasma physics. We include plasmons and transverse photon states. We show that field quantization in a plasma is equivalent to that of massive boson fields and discuss the qualitative differences with respect to standard quantization in a vacuum. We consider nonlinear effects and show that photon and plasmon charges can be associated with the ponderomotive force. We also discuss the conservation properties of these affective charges during nonlinear mixing processes. The existence of photon and plasmon charge and mass could be relevant to laboratory experiments and to astrophysics.